Social Media: A Bibliometric Analysis - Maharani, Siska; Lutpiani, Anisa; Setiawan, Adi (Malikussaleh University, Aceh, Indonesia, 2025)
This research discusses the development and role of social media in modern life, especially Within digital marketing and consumer behavior. Social media, defined as internet-based platforms that enable user creation and exchange of content, has experienced a rise from 2003 to 2013, with significant influence on communication, social interaction, and business strategy. The method used in this study is bibliometric analysis with VOSviewer software, which maps data from scholarly articles published in leading journals such as Elsevier, Emerald, Springer, Willey, Sagepub, and Taylor. Data was collected using Publish or Perish software with specific keywords related to social media, digital marketing, and consumer behavior. From the bibliometric analysis, 1,550 articles with 4,961 keywords were found and analyzed using co-occurrence and co-authorship methods, resulting in 111 specific keywords divided into 11 clusters. The study revealed the importance of social media in building customer-business relationships, the influence of the power of social ties on consumer behavior, and the role of social media in developing effective marketing strategies. The research also identifies author collaborations in social media-related studies and shows how research trends and patterns evolve. The findings provide deep insights into the use of social media in modern marketing strategies. They can form the basis for further research development in management, business, and digital marketing. The findings of this study offer valuable contributions to the academic and professional understanding of social media. They serve as a foundational reference for future research aiming to explore the strategic applications of social media in business, the psychology of online consumer engagement, and the technological advancements that continue to reshape digital communications. The study also provides insights into the evolution of research patterns, visualizing how scholarly focus has shifted from early platforms like MySpace and Flickr to contemporary and emerging platforms such as YouTube, TikTok, and Instagram. Using overlay visualization and keyword density maps, the research identifies recent trends and research gaps, highlighting areas that require further academic exploration. For instance, the dominance of